The Effect of Applying Sewage Sludge on Chromium and Copper Accumulation in Soil and Eucalyptus Camaldulensis in Fedio Plantation (Lattakia) (Latakia University Journal -Biological Sciences Series, 2018)
This study was carried out during 2013 – 2015 and aimed to assess the effects of applying dry sewage sludge on heavy metals accumulation (Chromium and Copper) in soil and plant tissues (leaf, trunk and litterfall) of Eucalyptus camaldulensis plantation established on sandy soil in Fedio plantation-Lattakia at April -2013. Four experimental treatments were compared at age 22 months: SS1 (sewage sludge 3 kg/tree), SS2 (sewage sludge 6 kg/tree), MF (mineral fertilizer), and C (no fertilizer or sludge applications). Application of sewage sludge significantly increased Cu concentration in the different parts of E. camaldulensis (leaf, trunk and litterfall) and soil in comparison with C and MF treatments, while Cr concentration in leaf and litterfall in SS2 treatment was significant higher than in SS1, MF and C treatments. أثر تطبيق حمأة الصرف الصحي على تراكم الكروم والنحاس في التربة والأوكاليبتوس المنقاري في مزرعة فديو (اللاذقية) أجريت هذه الدراسة بين عامي 2013 – 2015, وقد هدفت إلى تقييم الآثار الناتجة عن تطبيق حمأة الصرف الصحي الجافة على تراكم العناصر المعدنية الثقيلة (الكروم والنحاس) في كل من التربة والنبات (الأوراق, الجذع والفرشة الورقية) وذلك في مشجر للأوكاليبتوس المنقاري تم إنشاؤه على تربة رملية في مزرعة فديو (اللاذقية) في نيسان 2013. قمنا بمقارنة أربع معاملات تجريبية عند عمر 22 شهراً وهي:SS1  (حمأة صرف صحي 3 كغ/غرسة), SS2 (حمأة صرف صحي 6 كغ/غرسة), MF (سماد معدني), C (دون إضافة سماد أو حمأة. حيث أدى تطبيق حمأة الصرف الصحي إلى ازدياد في كمية النحاس في الأجزاء المختلفة للأوكاليبتوس المنقاري (الأوراق, الجذع والفرشة الورقية) والتربة في المعاملتين SS1 وSS2 وذلك بالمقارنة مع المعاملتين MF وC, بينما كان تركيز الكروم في الأوراق والفرشة الورقية في المعاملة SS2 أعلى بشكل ملحوظ من تركيزه في المعاملات SS1, MF وC.